Analysis of Non-Game Injuries in Major League Baseball. Issue 12 (27th December 2019) - Esquivel, Amanda; Freehill, Michael T.; Curriero, Frank C.; Rand, Kevin L.; Conte, Stan; Tedeschi, Thomas; Lemos, Stephen E.
Background: Numerous studies have investigated injuries and treatments in the baseball athlete. The majority of these studies have focused on the throwing shoulder and elbow. However, more recent literature is reporting injuries to other regions in this cohort, including the knee, head, hip, and hamstring. Purpose/Hypothesis: The purpose of the current study was to determine the number and type of injuries in Major League Baseball (MLB) and Minor League Baseball (MiLB) players that do not occur during the actual game but are related to baseball participation. Our hypothesis was that there would be a substantial number of injuries that occurred in professional baseball players during non-game situations. Study Design: Descriptive epidemiological study. Methods: Deidentified, anonymous data were collected from the 2011 through 2016 seasons from the MLB Health and Injury Tracking System (HITS) medical record database. All injuries that were identified as a primary diagnosis and resulted in at least 1 day out of play from both MLB and MiLB were examined. Injuries were categorized as occurring during the game ("game" injuries) or not during the game. A "non-game" injury was defined as occurring at any time other than during the scheduled game from the first to last pitch. Results: There were 51, 548 total injuries in MLB and MiLB players from 2011 to 2016, almost 40% of which were attributed to non–game-related injuries (n = 19, 201; 37.2%). The remainder occurred during a game (n = 32, 347; 62.8%). A significantly greater percentage of non-game injuries were season ending (10.8%) compared with the percentage of game-related season-ending injuries (8.4%) ( P < .0001). Pitchers had significantly more non–game-related injuries than game-related injuries ( P < .0001). Conclusion: A large number of injuries occur in professional baseball outside of actual games. MiLB players, specifically pitchers, are particularly at risk for these types of injuries. It is feasible that the overall injury rate in professional baseball players could be reduced by analyzing these injuries in more detail to develop prevention strategies.